Prevalence of anemia at diagnosis of pediatric chronic myeloid leukemia and prognostic impact on the disease course - Delehaye, Fanny; Rouger, Jérémie; Brossier, David; Suttorp, Meinolf; Güneş, Adalet Meral; Sedlacek, Petr; Versluys, Birgitta; Li, Chi Kong; Kalwak, Krzysztof; Lausen, Birgitte; Srdjana, Culic; Dworzak, Michael; et al. (Annals of hematology, 2023)
The clinical presentation of chronic myeloid leukemia (CML) at diagnosis differs in children compared to adults. At younger age, anemia appears to be frequent at diagnosis, but its prevalence and its impact on prognosis are not well known. In the International Registry of Childhood CML, we selected children and adolescents in chronic phase at diagnosis of CML and treated upfront with imatinib. We examined their hemoglobin level at diagnosis according to the WHO grades to assess the prevalence of anemia and its impact on response to tyrosine kinase inhibitors (TKIs). Data on 430 patients were included. Anemia at diagnosis was observed in 350 patients (81%), with a mean hemoglobin level of 96.4 g/l (SD 23.6). Among them, 182 patients (52%) presented with moderate anemia and 110 (31%) with severe anemia while 58 (17%) had mild anemia. Compared with mild and no anemia, moderate and severe forms were significantly associated with younger age at diagnosis, asthenia, splenomegaly, and increased leukocyte and basophil counts. Delays in achieving major and deep molecular responses were significantly increased for patients with moderate and severe anemia, and also failure of imatinib treatment was more frequent in these two sub-cohorts. However, hemoglobin level was not significantly associated with survival. Anemia at diagnosis of pediatric CML was frequent and may be considered as a prognostic factor.
Keywords: Humans; inhibitory proteinkinas; imatinib mesylát; dítě; prevalence; Child; Imatinib Mesylate; dospělí; Antineoplastic Agents; Hemoglobins; lidé; Children; Pediatric; Chronic myeloid leukemia; Adult; Protein Kinase Inhibitors; chronická myeloidní leukemie; Adolescent; prognóza; anemie; Anemia; protinádorové látky; Prevalence; Leukemia; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; hemoglobiny; Prognosis; mladiství